Recent ground thermo-hydrological changes in a Tibetan endorheic catchment and implications for lake level changes - Martin, Léo; Westermann, Sebastian; Magni, Michele; Brun, Fanny; Fiddes, Joel; Lei, Yanbin; Kraaijenbrink, Philip; Mathys, Tamara; Langer, Moritz; Allen, Simon; Immerzeel, Walter (HAL CCSD, 2022)
International audience Abstract. Climate change modifies the water and energy fluxes between the atmosphere and the surface in mountainous regions. This is particularly true over the Qinghai-Tibet Plateau (QTP), a major headwater region of the world, which has shown substantial hydrological changes over the last decades. Among them, the rapid lake level variations observed throughout the plateau remain puzzling and much is still to be understood regarding the spatial distribution of lake level trends (increase/decrease) and paces. The ground across the QTP hosts either permafrost or seasonally frozen ground and both are affected by climate change. In this environment, the ground thermal regime influences liquid water availability, evaporation and runoff. Therefore, climate-driven modifications of the ground thermal regime may contribute to lake level variations. For now, this hypothesis has been overlooked by modelers because of the scarcity of field data and the difficulty to account for the spatial variability of the climate and its influence on the ground thermo-hydrological regime in a numerical framework. This study focuses on the cryo-hydrology of the catchment of Lake Paiku (Southern Tibet) for the 1980–2019 period. We use TopoSCALE and TopoSUB to downscale ERA5 data and capture the spatial variability of the climate in our forcing data. We use a distributed setup of the CryoGrid community model (version 1.0) to quantify thermo-hydrological changes in the ground during the period. Forcing data and simulation outputs are validated with weather station data, surface temperature logger data and the lake level variations. We show that both seasonal frozen ground and permafrost have warmed (1.7 °C per century 2 m deep), increasing the availability of liquid water in the ground and the duration of seasonal thaw. Both phenomena promote evaporation and runoff but ground warming drives a strong increase in subsurface runoff, so that the runoff/(evaporation + runoff) ratio increases over time. Summer evaporation ...